7.071067812
Chat with our AI personalities
7
1/[5 + 3*sqrt(2)] = [5 - 3*sqrt(2)]/{[5 + 3*sqrt(2)][5 - 3*sqrt(2)]} = [5 + 3*sqrt(2)]/[25 - 18] = [5 - 3*sqrt(2)]/7
11*sqrt(8) + 6*sqrt(12) - 5*sqrt(2) = 11*sqrt(4*2) + 6*sqrt(4*3) - 5*sqrt(2) = 11*sqrt(4)*sqrt(2) + 6*sqrt(4)*sqrt(3) - 5*sqrt(2) = 11*2*sqrt(2) + 6*2*sqrt(3) - 5*sqrt(2) = 22*sqrt(2) - 5*sqrt(2) + 12*sqrt(3) = 17*sqrt(2) + 12*sqrt(3) and that cannot be simplified further.
sqrt(12)*2*sqrt(18)*sqrt(24) = sqrt(4*3)*2*sqrt(2*9)*sqrt(4*2*3) = sqrt(4)*sqrt(3)*2*sqrt(2)*sqrt(9)*sqrt(4)*sqrt(2)*sqrt(3) = 2*sqrt(3)*2*sqrt(2)*3*2*sqrt(2)*sqrt(3) = 24*sqrt(2)*sqrt(2)*sqrt(3)*sqrt(3) = 24*2*3 = 144
sqrt(10x)*sqrt(8x) = sqrt(80x2) = sqrt(16x2*5) = sqrt(16x2)*sqrt(5) = 4x*sqrt(5)